The golf ball method for rapid assessment of grassland structure. (8th April 2017) - Schultz, Nick; Keatley, Marie; Antos, Mark; Wong, Nathan; Moxham, Claire; Farmilo, Brad; Morgan, John W.
Summary: A key task for native grassland managers is to assess when biomass reduction is necessary to maintain plant and animal diversity. This requires managers to monitor grassland structure. Parks Victoria and La Trobe University developed a method for rapid assessment of grassland structure using golf balls. Baker‐Gabb et al . ( Ecological Management & Restoration, 17, 2016, p235) provide an example of where the method has been used to manage grassland structure to favour an endangered bird, the Plains‐wanderer ( Pedionomus torquatus ). In this study, we provide further critical analysis of the method using three data sets collected across different parts of Victoria that relate golf ball scores to various habitat attributes. We demonstrate how the golf ball score provides a good surrogate for key aspects of grassland structure. We show that the method does not provide a reliable surrogate for above‐ground biomass or vegetation cover, although we discuss how biomass and cover are not particularly good indicators of grassland structure. We argue that elements of grassland structure may be better correlated with desired conservation outcomes (e.g. plant species diversity or the presence of a particular species) than biomass or cover alone. We discuss examples of how the golf ball method has been used, and how it can be improved. The method will be particularly useful where a link can be demonstrated between golf ball scores and desired conservation outcomes, such as in the case of the Plains‐wanderer.